2016
DOI: 10.1007/s10803-016-2729-1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Autism Spectrum Disorder and Policing in England and Wales: Surveying Police and the Autism Community

Abstract: Experiences of autism spectrum disorder and policing in England and Wales: surveying police and the autism community. Journal of Autism and Developmental Disorders, 46(6), pp. 2028-2041. doi: 10.1007/s10803-016-2729 This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract An online survey gathered the experiences and views of 394 police officers (from England and Wales) regarding autism spectrum disorder (ASD). Just 42% of officers were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 23 publications
5
107
2
Order By: Relevance
“…This could be particularly relevant if the person's autism diagnosis is not disclosed to the jury. Indeed, many witnesses and defendants may be reluctant to share information about their autism diagnosis with criminal justice processionals, for example, due to concerns about justice professionals' perceived lack of autism of knowledge and awareness (e.g., Crane et al 2016) or fears that their diagnosis may count against them (e.g., Cooper and Allely 2017). It is, therefore, vital to examine the effects of providing jurors with knowledge of a witness' autism diagnosis, with or without the provision of additional information about the key characteristics of autism.…”
Section: Introductionmentioning
confidence: 99%
“…This could be particularly relevant if the person's autism diagnosis is not disclosed to the jury. Indeed, many witnesses and defendants may be reluctant to share information about their autism diagnosis with criminal justice processionals, for example, due to concerns about justice professionals' perceived lack of autism of knowledge and awareness (e.g., Crane et al 2016) or fears that their diagnosis may count against them (e.g., Cooper and Allely 2017). It is, therefore, vital to examine the effects of providing jurors with knowledge of a witness' autism diagnosis, with or without the provision of additional information about the key characteristics of autism.…”
Section: Introductionmentioning
confidence: 99%
“…This point raises a number of questions to consider, as previous research in the criminal justice field has suggested that autistic people are not always likely to disclose their diagnosis to professionals in that context (Crane et al, 2016). Many of our participants noted that they had little or no training or experience in identifying or dealing with cases involving autism.…”
Section: Practitioners' Experiencesmentioning
confidence: 83%
“…Parents are initially concerned about social development, but they also have worries about general delays and other specific problems (20,21). In addition, many of them have to wait a long time for diagnostic confirmation (22,23).…”
Section: Introductionmentioning
confidence: 99%